Forensic Study on Federal Road Pavement Failures at Rengit and Semerah, Batu Pahat - Sufiyanussuari, Syazwan Aiman; Ahmad Tajudin, Saiful Azhar; Yusof, Mohd Fairus; Yusoff, Nor Azizi (Journal of Sustainable Underground Exploration, 2021)
Forensic investigations in engineering term may be conducted to identify the causes of failure to facilitate the design of proper repairs, or to improve the performance or lifespan of a component, assembly, or structure. This paper presents the combination of geotechnical investigation and geophysical survey method as a forensic tool to predict the causes of pavement failure occurred along the coastal area of federal road FT005. The number and type of field testing are varying on each selected study area at Rengit and Semerah, Batu Pahat as this location constructed on soft soil area. Non-destructive testing (NDT) method using electrical resistivity tomography (ERT) were chosen to be applied at the worst severity of the road failure. Three number of resistivity lines of 100m and 200m were laid out using ABEM Terrameter LS2 with gradient method of electrode arrays covering up to 40-meters depth. Then, further testing of destructive testing (DT) method using borehole drilling conducted near the ERT lines to obtain soil profile with SPT N-value measurement. The disturbed and undisturbed samples were obtained to carried out laboratory test for soil classification. After that, visualization of road pavement layers was implemented via five number of trial pit test which were excavated up to subgrade layer to determine the thickness of the materials used in road construction. Three number of mackintosh probe test were also conducted on top of the subgrade layer after the trenching to obtain the strength of the subgrade layer. The results presented showed that severe longitudinal cracking were the predominant premature failures on the roads studied. This were found caused by settlement effect from the road subsidence from soft soil layer. The analysis obtained from RES2DINV program stated that the subsurface profiling was dominantly in saturated condition which the resistivity value was less than 100 ohm.m. From the SPT N-value it is observed that, the very soft soil layer is up to 8 m at it profile changes with depth from soft to stiff clays soil up to 40.5m. Another causes of failure were resulted from the differential settlement due to the effect of different design of road construction with varies material used. The reliability and efficiency of the instruments used were also discussed in this study.